Analysis of Project Delay in The Development of The Green Open Space at Kediri City Square Using the Earned Value Method - Datumarin, Fathia; Wibowo, Kartono; Soedarsono, Soedarsono (Jurnal Indonesia Sosial Sains, 2026)
This study adopts a quantitative case study approach using the Earned Value Method (EVM) to assess project cost and schedule performance, complemented by a Time–Cost Trade Off (Crashing Analysis) to formulate acceleration strategies that restore the project to its planned timeline. Primary data were collected through field observations and interviews, while secondary data were obtained from weekly and monthly reports, the project time schedule, and the Project Budget Plan (RAB). The analysis indicates that the project experienced delays, reflected by by the condition BCWP < BCWS, which reflects schedule deviation. However, cost utilization remains efficient because ACWP < BCWP, indicating that actual spending is lower than the value of work completed. This condition is supported by the cost performance index CPI > 1, which signifies cost efficiency, while the schedule performance index SPI < 1 indicates schedule delays. The estimated cost at completion (EAC), amounting to Rp13,125,412,382.00, shows that the project is expected to finish below the original budget of Rp17,968,594,000.00, whereas the time estimate (TE) shows a potential delay of 11.82 weeks beyond the contract duration. Through crashing analysis, adding 5 hours of overtime per day can reduce the remaining critical path duration from 11.82 weeks to 6 weeks with an additional cost of Rp143,390,625.00, equivalent to approximately 4.3% of the total crash cost.